2014
DOI: 10.1021/jm501051x
|View full text |Cite
|
Sign up to set email alerts
|

FPR2/ALXR Agonists and the Resolution of Inflammation

Abstract: The resolution of inflammation (RoI), once believed to be a passive process, has lately been shown to be an active and delicately orchestrated process. During the resolution phase of acute inflammation, novel mediators, including lipoxins and resolvins, which are members of the specialized pro-resolving mediators of inflammation, are produced. FPR2/ALXR, a receptor modulated by some of these lipids as well as by peptides (e.g., annexin A1), has been shown to be one of the receptors involved in the RoI. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
100
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(102 citation statements)
references
References 202 publications
1
100
0
1
Order By: Relevance
“…This structural modification was inspired by the observation that different aminoacid cores were well tolerated in other FPR2 agonists with ureidopropanamide structure [28]. For this purpose, we selected the commercially available 4-cyanophenylalanine and 3-pyridylalanine.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This structural modification was inspired by the observation that different aminoacid cores were well tolerated in other FPR2 agonists with ureidopropanamide structure [28]. For this purpose, we selected the commercially available 4-cyanophenylalanine and 3-pyridylalanine.…”
Section: Resultsmentioning
confidence: 99%
“…A wide range of chemically diverse non-peptidic FPR agonists have been identified so far [28], including benzimidazole derivatives exemplified by compound 1 [29], N -phenylurea derivatives (compound 2 ) [30], quinazolinones derivatives such as the highly specific non-peptide FPR2 agonist Quin-C1 ( 3 ) [31], and pyrazolone derivatives like the mixed FPR1/FPR2 agonist 4 (designated in most of publications as “Compound 43”) [32] (see Chart 1). Recently, we reported the identification of a group of 3-(1 H -indol-3-yl)-2-[3-(4-substituted-phenyl)ureido]propanamide derivatives as agonists of human FPR2, exemplified by compound 5 (Table 1, Chart 1) [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…LXA 4 attenuates neutrophil chemotaxis, respiratory burst, adhesion, and transendothelial migration, facilitates neutrophil apoptosis, stimulates macrophage clearance of apoptotic cells, suppresses IL-8 production, enhances airway epithelial tight junction formation, and augments repair of the bronchial epithelia. However, stable agonist analogs have been generated that mimic the effects of LXA 4 , making clinical evaluation a possibility (35,36). The half-life of LXA 4 is short, which makes it unusable as a therapeutic.…”
Section: Lipoxins and Resolvinsmentioning
confidence: 99%
“…The other group opposing these proinflammatory effects in synovial tissue is formed by anti-inflammatory mediators such as 15-LOX, formyl peptide receptor (FPR2), and IL-10 [6, 7]. Previous studies demonstrated that 15-LOX metabolites have potent anti-inflammatory actions on rheumatoid inflammation [8].…”
Section: Introductionmentioning
confidence: 99%